Dietary Supplementation of Nile Tilapia (Oreochromis niloticus) With Panax ginseng Essential Oil: Positive Impact on Animal Health and Productive Performance, and Mitigating Effects on Atrazine- Induced Toxicity - Ahmed, Mona M.; Mohammed, Amany T.; Farag, Mayada R.; Hassan, Mona A.; Mawed, Suzan A.; Alagawany, Mahmoud; Zizzadoro, Claudia; Di Cerbo, Alessandro; Abdel-Latif, Hany M. R. (Frontiers in Marine Science, 2022)
The present study assessed the impact of Panax ginseng essential oil (GEO) supplementation on physiological parameters related to productive performance and health status in Nile tilapia reared under standard conditions and exposed to a sub-lethal atrazine (ATZ) concentration. Fish were allocated into 6 groups, the control group was reared in clean water and fed a commercial basal diet (CNT), two groups were fed the basal diet supplemented with two different levels of GEO (GEO1 and GEO2, respectively), one group was intoxicated with 1/5 of ATZ 96-h lethal concentration 50 (1.39 mg/L) (ATZ group), and the remaining two groups were fed the GEO-supplemented diets and concurrently exposed to 1.39 mg ATZ/L (GEO1+ATZ and GEO2+ATZ, respectively). The experiment lasted for 60 days. GEO supplementation exerted a significantly positive influence on fish growth, feed utilization, and hepatic antioxidant defense systems at both levels of supplementation. ATZ exposure significantly reduced fish survival rates and impaired fish growth and feed utilization, with the lowest final weights, weight gain, total feed intake, and the highest feed conversion ratio being recorded in the ATZ-intoxicated group. ATZ exposure caused significant changes in intestinal digestive enzyme activity (decreased lipase activity), hematological indices (decreased hemoglobin, packed cell volume, erythrocytes, and leukocytes), blood biochemical variables (decreased total proteins, albumin, globulins, and immunoglobulin M; increased total cholesterol, triglycerides, and cortisol) and hepatic oxidative/antioxidant indices (decreased glutathione level, superoxide dismutase and catalase enzyme activity and mRNA expression levels, and increased malondialdehyde content). Moreover, in the hepatic tissue of ATZ-intoxicated Nile tilapia, histopathological alterations and upregulated mRNA expression levels of stress- and apoptosis-related genes (Hsp70, caspase 3, and p53) were observed. GEO supplementation in ATZ-treated groups significantly attenuated the aforementioned negative effects, though some parameters did not reach the CNT values. These findings provide further and partly new evidence that sub-lethal ATZ toxicity induces reduced survivability, growth retardation, impaired digestive function, anemia, immunosuppression, hepatic oxidative stress damage, and overall increased stress level in Nile tilapia, and suggest that GEO supplementation may be useful for mitigating this toxicity and provide more general support to productive performance and health status of this fish species.